Interaction Strategies of Haggling in the ‘Pawn Stars’ and ‘The Pickers’ TV Shows - Yapi Henri Wongkar; Ceisy Nita Wuntu; Devilito Prasetyo Tatipang; Imelda S. Lolowang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to investigate the Interaction strategies of haggling in the ‘Pawn Stars’ and ‘The Pickers’ TV shows. The participants are those who are involved in the interaction of haggling both in the TV shows. The instruments used for data collection in this qualitative study of sociopragmatics are video camera, television and computer. The data were collected through the video camera that was used to record the TV shows in the television and then the recorded TV shows in the video camera were transferred to the computer to be transcribed and analyzed. From the data analysis it is found out that buyers and customers often employ similar haggling strategies in some respects and distinctly different tactics in many other respects. Such strategies include humor, power, pleas and honorific tags. Therefore, it is expected that there will be other researches concerning this topic which involves much more comprehensive data or there will be other researches concerning the similar topic but at the different setting or participants. Keywords: Haggling, Interaction, Strategies, TV Shows